2021
DOI: 10.1155/2021/5537599
|View full text |Cite
|
Sign up to set email alerts
|

Completion Rates of Advance Directives in a Trauma Emergency Room: Association with Age

Abstract: Introduction An advance directive (AD) is a written legal document in which a person can express wishes and preferences for medical treatment for the moment when that person is no longer able to make medical decisions because of a serious illness or injury. While ADs have emerged in public, it is unclear, how many adults in Germany have completed an AD, and frequencies differ among different patient cohorts and medical settings. The aim of this study was to evaluate how many patients visiting a trauma emergenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…4 Other studies examining advance directives among trauma patients demonstrated an approximate rate of preinjury ADLC of 12%, which is greater than that noted in this study. 13,14 This study's demographics are consistent with those seen in other investigations of ADLC, with more advance directives held by female patients, individuals from White non-Hispanic race and ethnicity groups, and patients with preexisting comorbidities. 13,15,16 Despite the small number of patients who presented with ADLC, our study showed one intended benefit of advance care planning as patients with ADLC underwent WLSS approximately 24 hours earlier compared with those who did not have advance directives.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…4 Other studies examining advance directives among trauma patients demonstrated an approximate rate of preinjury ADLC of 12%, which is greater than that noted in this study. 13,14 This study's demographics are consistent with those seen in other investigations of ADLC, with more advance directives held by female patients, individuals from White non-Hispanic race and ethnicity groups, and patients with preexisting comorbidities. 13,15,16 Despite the small number of patients who presented with ADLC, our study showed one intended benefit of advance care planning as patients with ADLC underwent WLSS approximately 24 hours earlier compared with those who did not have advance directives.…”
Section: Discussionsupporting
confidence: 77%
“…Our results reveal that only a small percentage of older trauma patients have advance directives on file at the time of admission, which is significantly less than previous systematic reviews of advance directive completion 4 . Other studies examining advance directives among trauma patients demonstrated an approximate rate of preinjury ADLC of 12%, which is greater than that noted in this study 13,14 . This study's demographics are consistent with those seen in other investigations of ADLC, with more advance directives held by female patients, individuals from White non-Hispanic race and ethnicity groups, and patients with preexisting comorbidities 13,15,16 …”
Section: Discussionsupporting
confidence: 72%
“…In the current study, we demonstrated that the number of precautionary powers of attorney increased in parallel with the increasing prevalence of advance directives. Although completion rates of advance directives differ among patient subgroups and medical disciplines, recent data indicate an increasing number of patients to complete an advance directive in Germany [9,15,20,21]. Because all studies are descriptive in nature, it is unclear whether and to what extent factors like a new law or increased awareness in the media have contributed to this trend.…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing over the recent decade, completion rates of advance directives remain low in Germany [ 6 ]. Seniors seem to complete an advance directive more frequently compared to people in the working age [ 8 ]. However, there is also evidence that older people and patients with progressive comorbidities have thought about end-of life issues within their families and selected substitute decision makers, but most of them did not complete written documents or discuss their preferences with a physician [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promotion for completion of advance directives by legal reforms and informal support might have led to an increase of advance directive completion rates over the last decade [ 4 , 5 , 6 ]. However, completion rates of advance directives remain low in general [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%